2007
DOI: 10.1088/0031-9155/52/19/n04
|View full text |Cite
|
Sign up to set email alerts
|

A rapid, high sensitivity technique for measuring arsenic in skin phantoms using a portable x-ray tube and detector

Abstract: Using a portable x-ray tube and silicon PiN diode detector, an improved approach to the measurement of arsenic in skin phantoms was demonstrated. Skin phantoms of 8 mm thickness were made from polyester resin, with arsenic concentrations ranging from 0 to 30 microg g(-1). The excitation of characteristic arsenic x-rays was performed with the x-ray tube and K(alpha) x-rays were used as an indicator of arsenic concentration. From repeated phantom measurements, an instrumental minimum detection limit of 0.446 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 18 publications
(34 reference statements)
2
27
0
Order By: Relevance
“…The Ni and Cu characteristic x-ray detections shown in the larger spectrum must be interpreted with caution. It has been noted from previous experiments with the same system that trace amounts of Ni and Cu signal arise from the system itself (Fleming and Gherase, 2007;Fleming et al, 2013). Therefore, while part of the Ni and Cu signals observed here may derive from the rice sample, another component will be a consequence of alloys present likely in the collimator and detector housing.…”
Section: Resultsmentioning
confidence: 52%
“…The Ni and Cu characteristic x-ray detections shown in the larger spectrum must be interpreted with caution. It has been noted from previous experiments with the same system that trace amounts of Ni and Cu signal arise from the system itself (Fleming and Gherase, 2007;Fleming et al, 2013). Therefore, while part of the Ni and Cu signals observed here may derive from the rice sample, another component will be a consequence of alloys present likely in the collimator and detector housing.…”
Section: Resultsmentioning
confidence: 52%
“…This approach could develop as a new in vivo method for detecting arsenic in skin, lead in bone, and strontium in bone. [1] Phantom measurements have demonstrated the feasibility of portable XRF measurements of arsenic and selenium in skin, [2] nail, [3] and nail clippings, [4] along with lead in bone. [5] A recent in vivo study showed the capabilities of portable XRF with regard to assessing bone lead concentration in a human population.…”
Section: Introductionmentioning
confidence: 99%
“…A final example of a toxic measurement is arsenic, where the preferred site of measurement is skin. Development work has been performed by Studinski et al [12] and also by Gherase and Fleming [13]. This brief listing is not comprehensive, but it should provide an impression of the range of elements for which X-ray fluorescence measurement systems have been developed.…”
Section: Elements Measured In Vivo By X-ray Fluorescencementioning
confidence: 99%